PENERAPAN TEAMS GAMES TOURNAMENT (TGT) DENGAN BLENDED LEARNING TERHADAP HASIL BELAJAR PEMBELAJARAN FISIKA - Agatha Hadi Nugraha; Dwi Sulisworo; Arief Hermanto (Jurnal Dedikasi Pendidikan, 2021)
The sample in this study was class X IPA MA Madania Bantul, with 15 students. This type of research is quasi-experimental research. The data collection technique is using pretest, posttest. The results showed that the students' pretest, posttest mean scores were 73.53 and 81.93. Based on the classical N-Gain analysis results, it was found that an increase in gain of 0.31 was in the medium category. These results show that students show an increase in the use of the Teams games tournament learning model with blended learning in improving learning outcomes.